Drying under inert environment: the quality of Mango and Rockmelon - Hawlader, Mohammad Nurul Alam; Jiahe, Pan (IIUM Press, 2011)
Extensive tests were carried out on the quality related properties, such as flavor, appearance, texture and nutritional values of mango and rockmelon samples dried under normal air heat pump dryer (HPD), modified atmosphere heat pump dryer (MAHPD) using N2, and CO2 and also vacuum and freeze dryers. For mangoes and rockmelons, the MAHPD dried samples show better flavor than HPD dried samples. The freeze and vacuum dried samplcs are considered even better than MAHPD dried samples, although at a much higher costs. For MAHPD, N2, drying leads to a better color retention than CO2, drying. The HPD dried samples show a higher value of textural hardness than MAHPD samples, whereas the freeze dried samples show the lowest textural hardness. Freeze drying leads to the best vitamin C retention, followed by vacuum, MAHPD and HPD drying. In the case of MAHPD, the CO2, drying shows slightly higher retention of vitamin C than N2.